AN INTERACTIVE STUDENT WORKSHEET (LKPD) BASED ON AKM UTILIZE FLIPBOOK TO FACILITATE MATHEMATICAL UNDERSTANDING OF SOCIAL ARITHMETIC MATERIAL - Tomy Syafrudin; Tafsillatul Mufida Asriningsih; Nisatun Nahdliya; Nur Himmatul Ulya; Ulya Rofiqo; Anggun Zahrotun Habibah (Math Educa Journal, 2025)
The aim of this research is to describe and produce student worksheets that were valid, effective and practical to facilitate students' mathematical understanding. This research uses the ADDIE research and development model, which stands for Analysis, Design, Development, Implementation, and Evaluations, which goes through 5 stages, namely 1) analysis, 2) planning, 3) development, 4) implementation, and 5) evaluation. The worksheet was tested on a limited basis on six class VII students and a field trial on 24 class VII students at MTs Rahmat Sa'id. Data collection was carried out using worksheet validation sheets, student response questionnaires, educator response questionnaires, and mathematical understanding test sheets. Based on the validation results, the LKPD meets the valid criteria with a validity percentage of 82%. The LKPD also meets the practical criteria where the student response questionnaire score is 87.23% and the teacher response questionnaire score is 88,1%. The results of the LKPD effectiveness test seen from the results of the mathematical understanding test meet the effectiveness criteria with a score of 87,5%.